2014
DOI: 10.1093/infdis/jiu145
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Dampens Neutrophil-Mediated Inflammation in Methicillin-Resistant Staphylococcus aureus-Induced Pneumonia and Protects the Lung of Associated Damages

Abstract: Our results indicate that linezolid could be superior to vancomycin for the management of MRSA pneumonia by attenuating an excessive inflammatory reaction and protecting the lung from pathogen-associated damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Taken together, these results confirm that, compared with the control, CSE-USA300 is hypervirulent in mice, regardless of their genetic background, as exhibited by increased pulmonary CFUs at 24 hours PI. In response to USA300 infection, respiratory epithelial cells and AMs secrete cytokines and chemokines to induce inflammation (TNF-a, IL-1b) and recruit neutrophils (KC, MIP2) between 2 and 8 hours PI (36,37). Once recruited, neutrophils are the main source of proinflammatory cytokines and, thus, the sustained presence of activated neutrophils plays a central role in the development of acute lung injury (38).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results confirm that, compared with the control, CSE-USA300 is hypervirulent in mice, regardless of their genetic background, as exhibited by increased pulmonary CFUs at 24 hours PI. In response to USA300 infection, respiratory epithelial cells and AMs secrete cytokines and chemokines to induce inflammation (TNF-a, IL-1b) and recruit neutrophils (KC, MIP2) between 2 and 8 hours PI (36,37). Once recruited, neutrophils are the main source of proinflammatory cytokines and, thus, the sustained presence of activated neutrophils plays a central role in the development of acute lung injury (38).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only linezolid significantly decreased neutrophil infiltration in infected lung tissues, as documented by Ly6G-immunostaining. Consistently, it was concluded that, despite linezolid and vancomycin showed similar antibacterial activity in MRSAinfected lung, linezolid could be superior to vancomycin in MRSA pneumonia by modulating the inflammatory reaction and by protecting the lung from MRSA-associated damages [66].…”
Section: Linezolid Vs Vancomycin In the Treatment Of Mrsa-related Pnementioning
confidence: 86%
“…However, other authors have recently postulated that lung protection of linezolid from pathogen-associated damages in pneumonia could be related to the prevention of an excessive inflammatory response [66]. In a mouse model of MRSA-induced pneumonia treated with linezolid or with vancomycin, no difference was found between linezolid-treated and vancomycintreated animals in terms of decrease of bacterial burden in lung after 48 h of treatment.…”
Section: Linezolid Vs Vancomycin In the Treatment Of Mrsa-related Pnementioning
confidence: 92%
“…Given that HA-MRSA is substantially less virulent, it is difficult to establish a severe pneumonia model by transtracheal infection using HA-MRSA. A few studies have attempted to use a murine transtracheal pneumonia model of HA-MRSA (27)(28)(29) by inoculating a high load of MRSA (up to 10 7 to 10 9 CFU/mouse) via tracheal injection. At least 2 ϫ 10 9 CFU/mouse was necessary to induce lethal MRSA pneumonia, even in a neutropenic mouse model treated with cyclophosphamide (29).…”
Section: Discussionmentioning
confidence: 99%
“…Differential cell counts were performed by counting 100 cells. To validate the effect of antibiotics on inflammatory cytokines in this MRSA pneumonia model, we examined the concentration of two previously validated mouse cytokines (27,28,44), macrophage inflammatory protein-2 (MIP-2) and interleukin-6 (IL-6) using enzyme-linked immunosorbent assay (ELISA) kits (R&D Systems, Minneapolis, MN) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%